EXAMINING RESIDENT’S PERCEPTION OF SUSTAINABILITY TOURISM PLANNING AND DEVELOPMENT: THE CASE OF MALANG CITY, INDONESIA - Andy KURNIAWAN; Dahlan FANANI; SUPRIONO (Geo Journal of Tourism and Geosites, 2022)
Tourism development includes many studies on how planning and community views view the impact of tourism. This study presents the concept of tourism development that focuses on local people's perceptions of the impact of tourism. This study explores and explains the role of applied planning that affects the impact generated by tourism. The variables used in this study are key factors in supporting tourism development. This study uses a quantitative approach through statistical analysis of PLS-SEM and the distribution of a questionnaire that has been designed to 200 local communities. The sampling technique of this study used purposive sampling on local communities in tourist sites in Malang City. The findings show that optimal planning will support institutional stability which also has an impact on the perceived impact. This study contributes to broadening knowledge about the perceived impact of tourism by adding planning and stability aspects that are used to assess support for tourism development.